Прогнозування обсягів випуску вугільної продукції у повоєнний період в Україні - Makarov, Vitalii (General Energy Institute of the National Academy of Sciences of Ukraine, 2024)
The purpose of the study is to adjust the previously developed forecasts of the development of the Ukrainian coal industry, as well as to determine the appropriate volumes of coal production for the energy sector and the country's economy as a whole. Due to the loss of all mines in Luhansk region and some mines in Donetsk region as a result of Russia's full-scale invasion of Ukraine, the forecast scenarios for the development of the coal industry of Ukraine for the period up to 2040 were adjusted. To adjust the forecast scenarios for the development of the coal industry, the software subsystem for forecasting coal production in Ukraine was used in the context of instability of the structure of the country's fuel bases arising from the effect of extraordinary force factors, in particular martial law, temporary occupation of the territory of Ukraine, and the. The software was created to enable a quick assessment of the impact of emergencies situations in the country on production volumes in the coal industry and to take them into account when developing forecasts of fuel supply to the economy and the country's energy balance as a whole. The software is created on the basis of databases detailing professional forecasts of the coal industry development by coal mining facilities, taking into account mining, geological, technological, economic and social features of coal mining enterprises, as well as possible scenarios of their technological re-equipment and optimization of production sites, and allows adjusting such forecasts by changing the expected production status of a mine in the event of force majeure. According to the adjusted scenarios, the volumes of coal production to meet the needs of the thermal power industry, metallurgical industry and other sectors of the economy for the period up to 2040 were determined.